THE CRIMINAL LAW POLICY IN THE COUNTERMEASURES OF ANARCHIST DEMONSTRATION IN INDONESIA - sukriandi sukriandi (Journal Philosophy of Law, 2021)
Everyone has the right to freedom of expression, where the opinion referred to can be expressed either in writing or in the form of a statement in public. For an opinion expressed in public, one of them is by using a method in the form of a demonstration. Demonstrations in everyday reality often cause problems at the level of implementation. However, it is guaranteed in our constitution, the procedures and implementation of demonstrations often hurt the spirit of democracy itself. Demonstrations often turn into anarchic actions and violate the social order that has been built in society. As stated in the facts, the number of anarchic demonstrations has resulted in a lot of material and immaterial losses, where the safety of the residents around the demonstration site is not guaranteed. This is very contrary to the purpose of democracy as the basis for the demonstration, so it is necessary that if there is a policy formulation in overcoming demonstrations carried out in anarchism